If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9 + 2(x + -6) = 9 + -2(x + -9) Reorder the terms: 9 + 2(-6 + x) = 9 + -2(x + -9) 9 + (-6 * 2 + x * 2) = 9 + -2(x + -9) 9 + (-12 + 2x) = 9 + -2(x + -9) Combine like terms: 9 + -12 = -3 -3 + 2x = 9 + -2(x + -9) Reorder the terms: -3 + 2x = 9 + -2(-9 + x) -3 + 2x = 9 + (-9 * -2 + x * -2) -3 + 2x = 9 + (18 + -2x) Combine like terms: 9 + 18 = 27 -3 + 2x = 27 + -2x Solving -3 + 2x = 27 + -2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '2x' to each side of the equation. -3 + 2x + 2x = 27 + -2x + 2x Combine like terms: 2x + 2x = 4x -3 + 4x = 27 + -2x + 2x Combine like terms: -2x + 2x = 0 -3 + 4x = 27 + 0 -3 + 4x = 27 Add '3' to each side of the equation. -3 + 3 + 4x = 27 + 3 Combine like terms: -3 + 3 = 0 0 + 4x = 27 + 3 4x = 27 + 3 Combine like terms: 27 + 3 = 30 4x = 30 Divide each side by '4'. x = 7.5 Simplifying x = 7.5
| 3z-2(z-8)=2+2z | | 3.11+2.12=58 | | 6(4a+4b)-3(a+3b)= | | a+8=3a+4 | | 4(x-.8)=3.8x-5.8 | | 3(b+12)=8-4b | | 2w^2+11w-63=0 | | 120y^2-12y-5=0 | | 8-7a=4+3a | | 0.5(x+1)=0.2 | | 10x+4x+8-18=130 | | -(-8t+2)=-2(-10-5t) | | -9y-12=2y+21 | | -(8t+2)=-2(-10-5t) | | (5x+4)(3x^2-22+24)=0 | | (n+4)=6n+24 | | 40x-1-60x+6=0 | | 4x^3-9x^2=0 | | 5x+26=7x+5 | | -12x+48=0 | | 12+0.5+1x=16.75 | | 4t(13t+9)=0 | | -(7y+.6)=3.6-y | | 46=78+16n | | 8(x-3)+7=y | | 2(9c+2)= | | 8(x-3)=y | | 8x-3=y | | 2(b-8)= | | ln(1-x)+ln(4-x)=ln(10) | | 3x+46-x=58 | | 3(a+9)= |